PERAN KESULTANAN BANTEN DALAM MEMPERTAHANKAN DAN MENGEMBANGKAN NILAI-NILAI ISLAM DI NUSANTARA - Siti Nur Atika; Ishmatul Mawla; Siti Nurlatifah; Arizcha Marwatussoffah; Vera Oktaviani; Faiz Fikri Alfahmi (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
The Banten Sultanate played a strategic role in maintaining and developing Islamic values in the archipelago, especially in the coastal areas of West Java. Established in the 16th century, the Banten Sultanate functioned as a center for Islamic preaching and education, with the establishment of mosques and Islamic boarding schools as important symbols in the spread of Islamic teachings. Sultan Maulana Hasanuddin and his successors not only utilized political power, but also applied Islamic principles in government policies, making Islam the basis of morals and ethics in people's lives. Islamic boarding schools in Banten became centers of religious and cultural teachings, producing prominent scholars who spread Islam to other regions. Through an approach that integrated Islamic teachings with local culture, the Banten Sultanate succeeded in maintaining and introducing Islam as a religion that regulates all aspects of life, with an impact that is still felt today in Indonesia.